2006
DOI: 10.1590/s0074-02762006000600016
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hepatitis B and C virus markers among blood donors in Rio de Janeiro, Brazil, 1998-2005

Abstract: The prevalence of infection by hepatitis B (HBV) and C (HCV) viruses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
4
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 16 publications
(21 reference statements)
2
23
4
7
Order By: Relevance
“…The prevalence of positive serology for viral hepatitis found in this study is similar to those reported previously for Brazil by other authors (HBsAg: 0.14-0.78%, anti-HBc: 2.05-13.44%, anti-HCV: 0.34-1.14%) [46][47][48] . The prevalence of hepatitis B markers in Brazil varies greatly by region.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of positive serology for viral hepatitis found in this study is similar to those reported previously for Brazil by other authors (HBsAg: 0.14-0.78%, anti-HBc: 2.05-13.44%, anti-HCV: 0.34-1.14%) [46][47][48] . The prevalence of hepatitis B markers in Brazil varies greatly by region.…”
Section: Discussionsupporting
confidence: 91%
“…More studies are needed to explore this area using different methods of data collection. In addition, toothbrushes, razors, and some other house-holding instruments can transmit HBV within the family (16). In our study, it was found that 8% of involved patients gave a positive family history of HBV infection.…”
Section: Discussionmentioning
confidence: 55%
“…Although several studies have been conducted on hepatitis B and C, especially on blood banks 6,7,8,9,10,11,12 , there are few studies carried out among the general population 13,14,15 , and due to territorial extension, and cultural and economic differences, the distribution of these diseases in the country differs among regions 16 .…”
Section: Introductionmentioning
confidence: 99%